Strategi Kepemimpinan Kiai dalam Membentuk Karakter Aswaja - Rustam (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2020)
This study examines the Kiai's Leadership Strategy in Forming Aswaja's Character in An Nur Islamic Boarding School, Ngrukem, Bantul, Yogyakarta. This type of research was field research using a qualitative approach. Sources of data for this study were taken from data collection methods such as: first, direct observation or observation several times. Second, interviews with boarding school leaders, administrators, teachers, students, and residents around the boarding school. Third, documentation taken from field research studies with various related information. The results showed that all actions and activities carried out by the boarding school community (Dzuriyah Council, administrators, cleric, and students) at An Nur Islamic Boarding School, Ngrukem, Bantul, Yogyakarta not only memorized the Al-Qur'an, but also formed the character of Aswaja to the students.